The FOMC risk shift - Tim-Alexander Kroencke; Maik Schmeling; Andreas Schrimpf (Leibniz Institute for Financial Research SAFE, 2021)
We identify a component of monetary policy news that is extracted from high-frequency changes in risky asset prices. These surprises, which we call "risk shifts", are uncorrelated, and therefore complementary, to risk-free rate surprises. We show that (i) risk shifts capture the lion's share of stock price movements around FOMC announcements; (ii) that they are accompanied by significant investor fund flows, suggesting that investors react heterogeneously to monetary policy news; and (iii) that price pressure amplifies the stock market response to monetary policy news. Our results imply that central bank information effects are overshadowed by short-term dynamics stemming from investor rebalancing activities and are likely to be more difficult to identify than previously thought.
Keywords: G10; G12; E44; 330; Monetary Policy Surprises; Equity Premium; Fund Flows; Portfolio Rebalancing; Price Pressures